1980
DOI: 10.1177/002221948001300913
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Time Effect of Artificial Colors in Hyperactive Children

Abstract: F our previous studies from our laboratory have provided inconsistent data with respect to the role of artificial food colors on the behavior of hyperactive children. In the first study (Conners, Goyette, Southwick, Lees, & Andrulonis 1976), a significant improvement of behavior was found in children when on a food-additive-free diet compared with a control diet, but the effect was true for only one of the orders of treatment administration. A second study examined the effects of a challenge with artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The Feingold diet for ADHD was popularized by the media and accepted by many parents of ill children as a testament to this claim. Systematic reviews, however, showed that the diet was not effective and concluded that food additives do not cause ADHD (1).…”
Section: Biological Adversitymentioning
confidence: 99%
“…The Feingold diet for ADHD was popularized by the media and accepted by many parents of ill children as a testament to this claim. Systematic reviews, however, showed that the diet was not effective and concluded that food additives do not cause ADHD (1).…”
Section: Biological Adversitymentioning
confidence: 99%
“…In the 1970s and early '~O S , Conners undertook a series of studies assessing the effects of artificial colours on the behaviour of hyperactive children Conners et al , 1980Conners, 1980Conners, , 1981Conners, , 1989). These illustrate very well how, even when conducted by a sound and experienced clinical investigator, positive results in open studies cannot be reproduced with the same frequency in blinded challenge experiments, where placebo effects have been reduced or eliminated.…”
Section: K E Y W O R K O F C O N N E R Smentioning
confidence: 99%
“…To read more about this research see the following reviews: Arnold et al, 2 , Stevens et al, 3 Stevens et al, 4 Kanarek, 5 Weiss, 6 and Millichap and Yee, 7 and a 2012 meta analysis by Nigg et al 8 One thing that seems clear from the behavioral studies is that a greater proportion of children reacted to higher doses (≥50 mg) of AFCs 9-12 than to lower amounts (<50 mg). 13-19 Other important factors were age of the child (younger children were more reactive than older children) and time of evaluation (1-3 hours postchallenge were more revealing than later evaluations). Participants in these studies were thought by their parents to be reactive to AFCs and were diagnosed with “hyperkinesis,” “hyperactivity,” or “behavior problems,” which included restlessness, irritability, and sleep problems.…”
Section: Introductionmentioning
confidence: 99%